Pengaruh Model Discovery Learning Dengan E-Worksheet Geogebra Terhadap Hasil Belajar Persamaan Garis Lurus Siswa Kelas VIII MTs - Prihandini, Rafiantika Megahnia; Adawiyah, Robiatul (Universitas Nusa Cendana, 2025)
This study aims to analyze the effect of Discovery Learning with e-Worksheet GeoGebra on the learning outcomes of eighth-grade students at MTs AT-Taqwa Bondowoso. A quantitative study with a quasi-experimental design using a non-equivalent control group design was conducted with a control group (VIII D) and an experimental group (VIII C). The results of the study show that the use of e-Worksheet GeoGebra with the Discovery Learning method enhances student activity and learning outcomes. The homogeneity test (p = 0.155) and normality test (p > 0.05) indicated that the data were homogeneous and normally distributed. The gain score analysis showed a higher average score increase in the experimental group (11.81) compared to the control group (5.56). The posttest t-test (t = 3.8416, p = 0.001) and gain score t-test (t = 4.877, p = 0.000) showed significant differences between the two groups. Therefore, Discovery Learning using e-Worksheet GeoGebra has a significant effect and is more effective than the conventional method in improving student learning outcomes